Failure mode and effect analysis of subsea multiphase pump equipment - Oluwatoyin, S.K. (EDP Sciences, 2014)
Finding oil and gas reserves in deep/harsh environment with challenging reservoir and field conditions, subsea multiphase pumping benefits has found its way to provide solutions to these issues. Challenges such as failure issues that are still surging the industry and with the current practice of information hiding, this issues becomes even more difficult to tackle. Although, there are some joint industry projects which are only accessible to its members, still there is a need to have a clear understanding of these equipment groups so as to know which issues to focus attention on. A failure mode and effect analysis (FMEA) is a potential first aid in understanding this equipment groups. A survey questionnaire/interview was conducted with the oil and gas operating company and equipment manufacturer based on the literature review. The results indicates that these equipment's group are similar with its onshore counterpart, but the difference is the robustness built into the equipment internal subsystems for subsea applications. The results from the manufacturer perspectives indicates that Helico-axial multiphase pump have a mean time to failure of more than 10 years, twin-screw and electrical submersible pumps are still struggling with a mean time to failure of less than 5 years. Â© 2014 Owned by the authors, published by EDP Sciences.